The WDEP reality counseling to improve the students’ academic resilience - Tahir, Ahriyani; Sinring, Abdullah; Buchori, Sahril (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to examine the application of the WDEP Reality Counseling in enhancing academic resilience among students. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The study population consisted of 72 students, with a sample of 22 students divided equally into experimental and control groups (11 students each), selected through proportional random sampling. Data were collected using an academic resilience scale and observation guidelines. Data were analyzed using descriptive statistics and the Wilcoxon test. The findings revealed that: (1) At the pretest stage, both the experimental and control groups showed low levels of academic resilience. After the posttest, the academic resilience level in the experimental group increased to the high category, while the control group remained in the low category; (2) The implementation of the WDEP Reality Counseling was conducted according to five stages: rational treatment, want, doing, evaluation, and planning. Student participation during the counseling sessions was categorized as high; (3) There was a significant difference in academic resilience levels between the group that received WDEP Reality Counseling and the group that did not. This indicates that the application of tthe WDEP Reality Counseling significantly improves students' academic resilience.